Impact of early Adenotonsillectomy on Quality-of-Life improvement in Children with Obstructive Sleep Apnea: A Systematic Review and Meta-Analysis.: eAT in quality of life of pediatric OSA - Alotaibi, Meshari; Alobaysi, Sultan; Altammar, Mohammad; Alaklabi, Shafi; Aladhyani, Moath; Alruways, Osama; Alobaysi, Osama; Alruways, Abdulaziz; Alotaibi, Abdullah; Ali, Yousaf; Alotaibi, Salman (Saudi Medical Horizons Journal, 2025)
Obstructive sleep apnea syndrome (OSAS) in children is a prevalent pediatric illness, marked by partial or complete upper airway obstruction during sleep that significantly impacts quality of life. Adenotonsillectomy is the initial surgical treatment for kids with adenotonsillar hypertrophy. Nonetheless, AT's comparative effectiveness versus other therapies in terms of QoL improvement is contentious. This study systematically compares the effects of AT vs. WWST on QoL, cognition, and behavior in pediatric OSAS patients. A PRISMA-compliant systematic review and meta-analysis were conducted. The search was conducted across PubMed, Web of Science, Ovid Medline, Google Scholar, and ClinicalTrials.gov, encompassing studies published between 2000 and 2024. Studies were included if they reported QoL outcomes in pediatric OSAS patients comparing AT with WWST. Risk of bias was assessed using ROB 2 for randomized controlled trials (RCTs), and statistical analyses were performed using RevMan. Four RCTs (N=1436) met the inclusion criteria. AT significantly improved QoL, as measured by OSA-18 (pooled mean difference: -14.16[-25.40, -2.93]; P < 0.00001, I² = 79%) and PedsQL (pooled mean difference: 4.92 [3.37, 6.47]; P < 0.00001, I² = 0%). However, AT did not significantly improve cognitive and executive functions (BRIEF mean difference: -2.44 [-18.32, 13.44], P = 0.05, I² = 77%). Risk of bias showed variability in blinding and attrition rates. AT greatly enhances QoL in children with OSAS compared to WWST, while its effect on cognition and executive function remains uncertain. Long-term outcomes and cost-effectiveness should be addressed by future studies to inform clinical decision-making.